Penggunaan Metode Nāṭiq dalam Meningkatkan Mahārah al-Kalām di Nāṭiq International ‘Arabiyyah Course - Rahmanudin, Ii; Al Masyhuri, Amin (Study Program of Arabic Language Teaching, 2023)
Arabic language learning methods continue to evolve, so the Nāṭiq method is applied in one of the courses in Pare Kediri Nāṭiq International ‘Arabiyyah. This study will analyze how the use of the Nāṭiq method applied in one of the ciurses in Pare Kediri, precisely the Nāṭiq International ‘Arabiyyah Course, so that it can improve students' Arabic language skills and mental speaking. The method used in this study is a descriptive qualitative method with a phenomenological approach by describing and analyzing the phenomena that occur. The data collection technique uses observation, interviews, and documentation. The stages of data analysis use intuiting, describing, and analyzing. The results of this study are with the naatiq method, the students can speak Arabic well and fluently. This can be shown by students who follow the Arabic language learning program at Nāṭiq Internasional ‘Arabiyyah. There is an increase in mental speaking and Arabic language skills. The proof is that the three levels of Arabic language learners at Nāṭiq International ‘Arabiyyah, ranging from beginner, intermediate, and advanced levels, all passed with details of the beginner class: 1 person got a Fair grade, 3 people got a Good grade, and 7 people got a Very Good grade, then in the intermediate class 4 people got a Good grade and 8 people got a very good grade. And The advanced 2 people get Good grades, and 8 get Very Good. Therefore, the Nāṭiq Method is highly recommended in learning Arabic, especially in improving mental speaking skills.